Development and validation of measurement tools for user experience evaluation surveys in the public primary healthcare facilities in Greece: a mixed methods study - Kaitelidou, Daphne (BMC Fam Pract, 2019)
BACKGROUND: The public primary healthcare system in Greece has not been fully developed and is delivered by urban and rural health centers, outpatient departments in public hospitals and the recently established first-contact and decentralized local primary care units. The aim of this study was to develop a valid and reliable measurement tool for conducting periodic user experience evaluation surveys in public Primary HealthCare facilities in Greece such as outpatient clinics of public hospitals and health centers. METHODS: A mixed methods approach was applied. In particular, the methodology of developing and validating the tools included three steps: (a) establishment of the theoretical background/literature review, (b) qualitative study: development of the tools items and establishment of the face validity and (c) quantitative study: pilot testing and establishment of the structural validity and estimation of the internal consistency of the tools. Two patient focus groups participated in qualitative study: one visiting health centres and the other visiting the outpatient clinics of public hospitals. Quantitative study included 733 Primary Health Care services’ users/patients and was conducted during August–October 2017. Exploratory and confirmatory factor analysis was performed to check for structural validity of the tools, while Cronbach’s alpha coefficients were estimated to check for reliability. RESULTS: Confirmatory factor analysis confirmed almost perfectly the presumed theoretical model and the following six factors were identified through the tools: (a) accessibility (three items, e.g. opening hours), (b) continuity and coordination of care (three items, e.g. doctor asks for medical history), (c) comprehensiveness of care (three items, e.g. doctor provides advices for healthy life), (d) quality of medical care (four items, e.g. sufficient examination time), (e) facility (four items, e.g. comfortable waiting room) and (f) quality of care provided by nurses and other health professionals (four items, e.g. polite nurses). CONCLUSIONS: We have developed reliable and valid tools to measure users’ experiences in public Primary HealthCare facilities in Greece. These tools could be very useful in examining differences between different types of public Primary Health Care facilities and different populations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12875-019-0935-6) contains supplementary material, which is available to authorized users.